Exclusion from hexagonal mesophase surfactant domains drives end-to-end enchainment of rod-like particles - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen, Debasis; Bhagavatula L. V. Prasad; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2013)
Anisotropic rod-like particles assemble end-to-end when the surfactant/water matrix in which they are dispersed is cooled from the isotropic to the lyotropic hexagonal phase. We demonstrate the formation of such end-to-end assemblies for gold nanorods, which are tens of nanometers in size, as well as for micrometer-sized ellipsoidal polystyrene particles. In both cases, the particles are well-dispersed in the low-viscosity surfactant/water phase above the isotropic-H-1 transition temperature. On cooling into the H-1 phase, mesophase domains form and the particles are expelled to the isotropic phase. As the H-1 domains grow and finally impinge, the particles are localized at the domain boundaries where they reorient and assemble end-to-end. Remarkably, we observe the formation of end-to-end assemblies of gold nanorods even for volume fractions as low as 2 x 10(-6) in the initially dispersed state. The extent of particle ``enchainment'' increases with the particle concentration and with the aspect ratio of the particles.

Enhancing cubosome functionality by coating with a single layer of poly-epsilon-lysine - Deshpande, Sonal; Venugopal, Edakkal; Ramagiri, Shobha; Bellare, Jayesh R.; Kumaraswamy, Guruswamy; Singh, Neetu (ACS Applied Materials & Interfaces, 2014)
We report the preparation and characterization of monoolein cubosomes that can be easily surface modified through adsorption of a single layer of cationic poly-epsilon-lysine. Poly-epsilon-lysine coated cubosomes show remarkable stability in serum solution, are nontoxic and, are readily internalized by HeLa cells. The poly-epsilon-lysine coating provides chemical handles for further bioconjugation of the cubosome surface. We also demonstrate that the initial release rate of a hydrophilic drug, Naproxen sodium, from the cubosomes is retarded with just a single layer of polymer. Interestingly, cubosomes loaded with Naproxen sodium, recently shown to have anticancer properties, cause more apoptosis in HeLa cells when compared to free unencapsulated drug.
Keywords: bioconjugation; cubosomes; drug delivery vehicle; dual loading; theranostics

Elastic compressible energy storage devices from ice templated polymer gels treated with polyphenols - Das, Chayanika; Chatterjee, Soumyajyoti; Kumaraswamy, Guruswamy; Krishnarnoorthy, Kothandam (Journal of Physical Chemistry C, 2017)
Design and fabrication of rechargeable energy storage devices that are robust to mechanical deformation is essential for wearable electronics. We report the preparation of compressible supercapacitors that retain their specific capacitance after large compression and that recover elastically after at least a hundred compression expansion cycles. Compressible supercapacitors are prepared using a facile, scalable method that readily yields centimeter-scale macroporous objects. We ice template a solution of polyethylenimine in green tea extract to prepare a macroporous cross-linked polymer gel (PG) whose walls are impregnated with green tea derived polyphenols. As the PG is insulating, we impart conductivity by deposition of gold on it. Gold deposition is done in two steps: first, silver nanoparticles are formed on the PG walls by in situ reduction by polyphenols and then gold films are deposited on these walls. Gold coated PGs (GPGs) were used as electrodes to deposit poly(3,4-ethylenedioxythiophene) as a pseudocapacitive material. The specific capacitance of PEDOT coated GPGs (PGPG) was found to be 253 F/g at 1 A/g. PGPG could be compressed and expanded over a hundred cycles without any suffering mechanical failure or loss of capacitative performance. The capacitance was found to be 243 F/g upon compressing the device to 25% of its original size (viz. compressive strain = 75%). Thus, even large compression does not affect the device performance. This device shows power and energy densities of 2715 W/kg and 22 Wh/kg, respectively, in the uncompressed state. The macroporous nature of PGPG makes it possible to fill the PGPG pores with gel electrolyte. We report that the gel electrolyte filled supercapacitor exhibited a specific capacitance of 200 F/g, which increased by 4% upon 75% compression.

Effect of electrostatic interactions on structure and mechanical properties of ice templated colloid-polymer composites - Suresh, Karthika; Kumaraswamy, Guruswamy (Journal of Physics D-Applied Physics, 2019)
When an aqueous dispersion of negatively charged colloids, cationic polymer and crosslinker is frozen and the polymer is allowed to crosslink in the frozen state, we obtain a self-standing macroporous composite foam. This material is soft, despite the high concentration of colloids and yet is remarkably elastic to large compressive strains. In these macroporous composites, the pore walls comprise colloidal particles held within a crosslinked polymer network. Here, we investigate the effect of varying colloid- polymer interactions in pre-fabricated macroporous composites on their microstructure and mechanical properties. During preparation of the composite, cationic polymer adsorbs on the negatively charged colloids. We tune the surface charge of particles embedded in a macroscopic monolith by immersing the composites in water maintained at different pH. In this way, we tune polymer-particle interactions in the composite. We observe a sudden increase in interparticle distance and swelling of composite when pH is decreased below the particle's isoelectric point. Correspondingly, we observe reduction in Young's and shear moduli, compression strength and macroscopic energy dissipation. We did not observe any pH dependent changes in pure polymer sponges (prepared by ice templating and crosslinking a polymer solution that does not contain colloidal particles). Therefore, the pH dependent structural and mechanical property changes arise from the composite structure rather than purely from the crosslinked polymer. We believe that the reduction in mechanical stiffness when the polymer-particle interaction becomes repulsive is because of the reduction in interfacial contacts between particle and polymer. Therefore, the mechanical stiffness of ice templated composite is strongly influenced by interactions between the polymer and particle surface.
Keywords: colloid; electrostatic interaction; ice templating; mechanical properties; Polymer

Elastic piezoelectric aerogels from isotropic and directionally ice-templated cellulose nanocrystals: comparison of structure and energy harvesting - Ram, Farsa; Biswas, Bipul; Torris, Arun; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Cellulose, 2021)
We report the preparation of highly compressible and elastic piezoelectric aerogels of carboxylated cellulose nanocrystals (CNCs). Aqueous CNC dispersions containing polyethyleneimine and crosslinker were frozen isotropically to yield isotropic aerogels, while oriented aerogels were prepared by directional freezing. These aerogels were highly flexible and porous (similar to 85% void fraction), exhibiting greater than 90% recovery at 50% compressive strain even after 100 compression-decompression cycles. Since such aerogels with low bulk modulus and high anisotropy would be an ideal platform for leveraging the piezoelectric properties of CNCs, we used them to prepare piezoelectric nanogenerator devices and determined their energy transduction behavior. Anisotropic aerogels led to an enhanced open-circuit voltage of 840 mV (at similar to 8 N applied force), which is over 2.6 times higher than isotropic aerogels (320 mV). The energy density of anisotropic aerogels was around 52 nW/cm(2), representing outstanding piezoelectric performance for cellulose-based aerogels. Such aerogels with high compressibility, elastic recovery and exceptional piezoelectric performance could have potential applications in sensors, wearable electronics, etc.
Keywords: Aerogel; Anisotropic; Cellulose nanocrystals; energy harvesting; Piezoelectricity